The Effect of Verbal Task Instruction on Spatial-Numerical Associations of Response Codes Effect Coding of Spatial-Numerical Associations: Evidence From Event-Related Potential - Pan, Yun; Zhang, Zhiwei; Li, Wei; Zhao, Xiaoxiao (Frontiers in Neuroscience, 2022)
The spatial-numerical associations of response codes (SNARC) reveals that individuals can represent numbers in space. In this study, event-related potential (ERP) technology was used to probe the effect of verbal-spatial task instructions on spatial-numerical associations coding by using digit parity and magnitude judgment tasks, with numbers 1–9 (except 5) and Chinese word labels (“left” and “right”) as experimental materials. The behavioral results of Experiment 1 showed that the SNARC effect was mainly based on verbal-spatial coding, and the SNARC effect appeared when stimulus onset asynchronys (SOAs) was 0 ms; ERP results did not reveal that the SNARC effect coding appeared at any specific stage. The behavioral results of Experiment 2 showed that the SNARC effect was dominated by verbal-spatial coding; ERP results showed that significant verbal-spatial coding was found in the early positive deflection of stimulus-locked lateralized readiness potential (S-LRP), and significant verbal-spatial coding was found in the latency of response-locked LRP (R-LRP). The results show that the encoding mode of the SNARC effect is influenced by the processing degree of the word labels, the encoding of the SNARC effect is produced in the early perceptual stage, and the specific performance is an extension of the response-related stage. The characteristics of SOAs and target numbers affect the generation of the SNARC effect.